Examining patient–provider relationship (PPR) quality and patient activation in the Medicare population - Mattingly, T. Joseph; Tom, Sarah E.; Stuart, Bruce; Onukwugha, Eberechukwu (Aging clinical and experimental research, 2017)
Background Patient activation describes an individual’s willingness and ability to take actions to independently manage health. Additional qualities of the relationship between a patient and provider may play a role in patient decision-making and motivation. Aims (1) To describe patient characteristics for groups who perceive different quality levels of PPR. (2) To examine the association and determine the effect of PPR on patient activation. Methods The Medicare Current Beneficiary Surveys was used to gather information on patient confidence, information seeking behaviors, and PPR. Scores for each variable set were categorized and described. Odds ratios were calculated using multinomial logistic regression models adjusting for sociodemographic variables. Results The study included 15,185 beneficiaries, 4198 (27.6 %) were categorized as low PPR, 6752 (44.5 %) were moderate PPR, and 4235 (27.9 %) high PPR. Adjusting for covariates, patients with moderate PPR and high PPR were more likely to have higher confidence when making healthcare decisions and exhibit information seeking behaviors compared to low PPR beneficiaries. Discussion This study supports the notion that patients with stronger relationships with their providers are also more active in healthcare decisions. After adjusting for gender, race, age, education, and income, high-quality PPR was still found to be associated with increased levels of activation in the Medicare population. Conclusions High-quality patient–provider relationships are associated with improved patient confidence and information seeking behaviors. Provider-centered strategies to improve patients’ connections to their physicians may motivate patients to engage in the healthcare process.